(untitled) (Revista Direito em Debate, 2024)
The article addresses freedom as a fundamental value in the Federal Constitution, emphasizing the protection of dignity and personality rights of people and vulnerable groups, in the face of hate speech. The general objective is to understand the potential for violence resulting from bellicose language, especially against vulnerable minorities. Discusses how oppressive language can lead to physical violence, including in the digital environment. The text is divided into two well-defined sections, which correspond to its specific objectives: initially, it seeks to clearly understand freedom of expression and thoughts, with its constitutional limitations and implications for personality law; the second part analyzes hate speech as an act that precedes acts of violence. Finally, a conclusive synthesis of the reflections that were formed throughout the text is presented to verify the hypothesis initially admitted, in the sense that yes, hate speech must be combatted, because it serves as a trigger that can trigger acts of violence against vulnerable groups. The research was viewed using the hypothetical deductive method and analyzed the specialized doctrine on the subject, with the applicable legislation, analysis of cases taken from the Supreme Court of the United States to emphasize the degree of freedom of expression that is attributed there to cases similar to what is presented on Brazilian soil by the Judiciary.